EXPERIÊNCIA MÍSTICA E FILOSOFIA EM PLOTINO - Bernardo Guadalupe dos Santos Lins Brandao (2007)
Plotinus was not only a mystic, but also a platonic philosopher: he not only tried to express his mystical experiences in his texts, but he also formulated a philosophic of the mystic union. This dissertation is an attempt to expose the plotinian theory of the mystical union and the accounts of the experience. As in the texts of Plotinus there is notonly a kind of mystical experience, but two (the experience of the mystic union of the soul and the Intellect and of the soul with the One), this research focuses in four main areas: the theory of the mystical union of the soul with the Intellect; the experience of this union; the theory of the mystical union of the soul with the One; the experience of this union.